The Dynamics of Land Use Change in Metropolitan Areas: The Impact of Urbanization and Sustainable Management Strategies - Lasaiba, Mohammad Amin (Universitas Pattimura, 2024)
Land use change is a global phenomenon with significant impacts on the environment, society, and economy, especially in metropolitan areas experiencing rapid urbanization. This study aims to analyze the dynamics of land use change, the driving factors, and the resulting ecological and socio-economic impacts. The method used in this research is a literature review with a qualitative approach. Data were collected from various secondary literature sources, including books, journal articles, research reports, and dissertations relevant to the research topic. The findings indicate that urbanization is the primary driver of land use change, leading to the conversion of green spaces such as forests and agricultural land into urban areas. The impacts of these changes include air quality degradation, increased flood risk, soil degradation, and loss of biodiversity. Case studies in cities such as Jakarta, Bangkok, and Manila illustrate how rapid urbanization transforms urban landscapes and creates complex environmental challenges. This research emphasizes the importance of sustainable land management through the application of landscape-based models that integrate spatial and temporal data to predict future land use changes. Evidence-based policy recommendations are provided to support more sustainable and environmentally friendly development. The results of this study are expected to contribute to the development of theory and practice in land use change studies and provide a framework that can be applied in various geographical and socio-economic contexts.